Community-based human resource transformation in remote coastal tourism development in south nias - Timotius Duha (Institute of Computer Science (IOCS), 2026)
This study examines community-based human resource transformation in coastal tourism development within remote coastal communities in South Nias, Indonesia. Coastal tourism is increasingly recognized as a strategic driver of regional economic growth, poverty reduction, and community empowerment. However, tourism development in remote areas often encounters challenges such as limited human resource capacity, low community participation, and dependence on external actors. This research explores how local communities transform their human resources to become active agents of sustainable tourism development. A qualitative approach was employed in Soto'ó Village, Maniamolo Sub-district, South Nias Regency. Data were collected through semi-structured interviews, direct observation, and documentation involving community leaders, tourism actors, village officials, youth groups, women's groups, and local entrepreneurs. Data analysis focused on community experiences, social interactions, and collective learning processes. Findings indicate that Sotoó Village has a passion for promoting tourism, but limited human resources and minimal human resource development require improvement and restructuring through human resource transformation, such as awareness transformation, competency development, strengthening social capital, the emergence of community leadership, and socio-economic empowerment. This study proposes a Community-Based Human Resource Transformation model that emphasizes participatory governance, leadership development, and collaborative stakeholder engagement as the primary foundation for sustainable coastal tourism development